Synthesis and biophysical properties of tetravalent PEG-conjugated antisense oligonucleotide. (15th January 2023) - Rahman Chowdhury, Taslima; Taufiq, Tahia; Ishida, Kenta; Ariful Islam, Md; Kasahara, Yuuya; Osawa, Takashi; Obika, Satoshi
Graphical abstract: Abstract: This study was aimed at developing a novel platform for tetravalent conjugation of 4-arm polyethylene glycol (PEG) with an antisense oligonucleotide (ASO). The ASO technology has several limitations, such as low cellular uptake, poor nuclease stability, and short half-life. PEG-conjugated ASOs may result in an improvement in the pharmacokinetic behavior of the drug. Moreover, PEGylation can reduce enzymatic degradation and renal excretion of the conjugates, thereby, increasing its blood stability and retention time. In this study, we successfully synthesized PEG-ASO conjugate consisting of 4-arm-PEG and four molecules of ASO (4-arm-PEG-tetra ASO). Its hybridization ability with complementary RNA, enzymatic stability, and in vitro gene silencing ability were evaluated. No significant difference in hybridization ability was observed between 4-arm-PEG-tetra ASO and the parent ASO. In addition, gene silencing activity of the 4-arm-PEG-tetra ASO was observed in vitro . However, the in vitro activity of the 4-arm-PEG-tetra ASO was slightly reduced as that of the parent ASO. Moreover, the 4-arm-PEG-tetra ASO showed appreciable stability in cellular extract, suggesting that it hybridizes with mRNA in its intact form, without being cleaved in the cell, and exhibits ASO activity.